2002
DOI: 10.2527/2002.8092433x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of soy oligosaccharides on apparent and true ileal amino acid digestibilities and fecal consistency in growing pigs

Abstract: Fourteen ileally cannulated pigs (BW = 35 +/- 2 kg) were randomly allotted to a replicated 7 x 7 Latin square design experiment to evaluate the influence of the soybean oligosaccharides (OS), raffinose and stachyose, on ileal nutrient digestibility and fecal consistency. Semipurified diets containing soy protein concentrate (SPC) or soybean meal (SBM) as the sole protein sources were fed. Soy solubles (SS), a by-product of SBM processing containing 3.5% raffinose and 11.5% stachyose, were used to increase diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
3
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 25 publications
3
72
3
1
Order By: Relevance
“…1 Casein (control) diet was used to determine basal loss and digestibility, according to the formulations of Moughan and Schuttert (1991) and Smiricky et al (2002).…”
Section: Ileal Aa and Protein Digestibilitymentioning
confidence: 99%
“…1 Casein (control) diet was used to determine basal loss and digestibility, according to the formulations of Moughan and Schuttert (1991) and Smiricky et al (2002).…”
Section: Ileal Aa and Protein Digestibilitymentioning
confidence: 99%
“…Free monosaccharides were injected at a volume of 25 µL. All assays were conducted using a CarboPac PA-1 column and guard column following methods cited by Smiricky et al (13).…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study, although significant oligosaccharide hydrolysis in the chicken gut was achieved (57%), no improvement in growth performance was noted (Slominski et al, 2006). In a study with cannulated young pigs, soy oligosaccharides reduced nutrient digestibility, but the reduction was small, ranging from 1.1 to 7.4 percentage units (Smiricky et al, 2002). The results of another experiment with growing pigs indicated that the ileal digestibility of -galactosides added to a semi-purified diet was higher than 75% (Smiricky-Tjardes et al, 2003).…”
Section: Physiological Properties Of α-Galactosides In the Gastrointementioning
confidence: 89%